THE MAIN TYPES AND PRODUCTIVITY OF FLORA COMPONENTS IN GERMAN AND UZBEK PHRASEOLOGISMS - Khamidova Tilovatkhon Rakhmatjonovna (Modern American Journals, 2025)
This article presents the main types and productivity of floral components in German and Uzbek phraseological units, modern approaches to studying their national-cultural characteristics, the scientific works and opinions of scholars in this field, as well as a comparative analysis of some phraseological units containing floral components in the German and Uzbek languages.
Keywords: Phraseological unit, floral component, national-cultural characteristics, comparative analysis, phraseological composition, cognitive approach